The Figure in the Carpet - Lurbe, Pierre (Hungarian Journal of English and American Studies, 2021)
Book review: Győri, Zsolt, and Gabriella Moise, eds. Travelling around Cultures: Collected Essays on Literature and Art. Newcastle upon Tyne: Cambridge Scholars, 2016. xii + 279 pages. ISBN 978-1-4438-0996-2. Hb. £52.99.